Pastoral care in old age psychiatry: Addressing the spiritual needs of inpatients in an acute aged mental health unit. (11th December 2012) - Goh, Anita M.Y.; Eagleton, Tamara; Kelleher, Rosemary; Yastrubetskaya, Olga; Taylor, Michael; Chiu, Edmond; Hamilton, Bridget; Trauer, Tom; Lautenschlager, Nicola T.
Abstract Introduction Pastoral Care (PC) practitioners respond to the spiritual needs of patients and families of all spiritual orientations. The integrated PC service in an acute psychogeriatric inpatient ward at St Vincent's Aged Mental Health Service, Melbourne, Australia, was examined to investigate how PC was being accessed by inpatients. Methods A retrospective medical record file audit was undertaken of patients admitted over a 16‐month period from 1 February 2009 to 30 June 30 2010 (n = 202). Results Sixty‐eight percent were seen by PC practitioners during their admission. Sixty‐six percent received PC assessments, 32% received PC ministry, and 10% received PC ritual or worship interventions. Other interventions (counseling/education, crisis situation, grief/ bereavement counseling) occurred infrequently. Seventy‐five percent of Roman Catholic patients received PC compared to 57% of those patients with no religious affiliation. However, the overall association between religious grouping and receiving PC was not significant. Gender, religion, marital status, legal status, country of birth, language spoken, living situation, carer needs, or educational level were not related to PC contact. Whether or not an inpatient received PC assessment was unrelated to diagnostic category. Patients seen by PC were significantly more likely to engage in religious practice, have longer length of stay, and have neuropsychological, social work and occupational therapy assessments. Discussion Results suggest that PC practitioners can help optimize the clinical care of patients by developing a comprehensive understanding of their spiritual and religious needs and providing a more holistic service.